2018
DOI: 10.1021/acs.chemrestox.8b00066
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Metabolomics and Proteomics Approach To Identify Metabolic Abnormalities in Rats with Dioscorea bulbifera Rhizome-Induced Hepatotoxicity

Abstract: Previous studies have shown that Dioscorea bulbifera rhizome (DBR) can induce hepatotoxicity in clinical practice. However, its underlying mechanisms remain largely unexplored. In the present study, we investigated the global effect of DBR exposure on the proteomic and metabolomic profiles in rats over a 12-week administration using an integrated proteomics and metabolomics approach. The abundance of 1366 proteins and 58 metabolites in the liver of rats after subchronic exposure to DBR was dose-dependently alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Except for this discrepancy, all other results indicated the active involvement of energy metabolism in the host reaction to the S. japonicum infection. In addition, pyrimidine metabolism was reported to play important roles in DNA and RNA biosynthesis (Tian et al, 2018;Zhao et al, 2018), therefore the changes in pyrimidine metabolism we identified in this study may suggest the potential effects on DNA and RNA biosynthesis caused by S. japonicum infection in mice.…”
Section: Disturbed Metabolic Pathways Associated With S Japonicum Infectionmentioning
confidence: 73%
See 1 more Smart Citation
“…Except for this discrepancy, all other results indicated the active involvement of energy metabolism in the host reaction to the S. japonicum infection. In addition, pyrimidine metabolism was reported to play important roles in DNA and RNA biosynthesis (Tian et al, 2018;Zhao et al, 2018), therefore the changes in pyrimidine metabolism we identified in this study may suggest the potential effects on DNA and RNA biosynthesis caused by S. japonicum infection in mice.…”
Section: Disturbed Metabolic Pathways Associated With S Japonicum Infectionmentioning
confidence: 73%
“…As reported in the previous study, uridine as a pyrimidine nucleoside, is the material basis of RNA synthesis, the bioavailability of which is particularly crucial to the synthesis of RNA and bio-membranes and the post-translational modification of protein (via the formation of pyrimidine nucleoside-lipid conjugates/UDP-sugar conjugates; Kurland et al, 2015 ; Cicuéndez et al, 2018 ; Tian et al, 2018 ). Uridine was also reported to exert protective effects against hepatotoxicity ( Zhao et al, 2018 ). Therefore, the reduction of uridine in our study may indicate that the DNA and RNA synthesis was disturbed in the host and liver toxicity was induced by the infection ( Zhou et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The system was conducted with a Gersted multipurpose Sample mps2 with dual heads (Gerstel, Muehlheim, germang) and an Agilent 7890B gas chromatography. As previously described, the sample preparation procedures was executed 11,12 . Furthermore, to ensure consistently high quality of data, an extensive series of quality control (QC)/assurance procedures was employed.…”
Section: Gc-ms-based Metabolomic Analysismentioning
confidence: 99%
“…The correlation network diagram established by OmicBean software (a web-based software application for interacting multi-omic data and available from http://www.omicsbean.cn/) can display moxibustion-intervened differentially expressed metabolites, DEPs, and signi cantly perturbed signaling pathways through visual interaction. The protein-metabolite interaction network was generated with a score of ≥ 2, number of nodes>60 and p-value < 0.05 [44]. Finally, the hierarchical cluster analysis of identi ed proteins and metabolites was employed by MEV software (version 4.9.0).…”
Section: Integrated Analysis Of Metabolomics and Proteomicsmentioning
confidence: 99%